Analysis Of Stock Control Of Raw Materials Of Dzohir Noodles In Bengkulu - Ahmelia, Monika; Herlin, Herlin; Rahman, Abdul (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This study aims to analyze the stock inventory control of Mie Dzohir’s raw materials in Bengkulu. The analytical method used is Economic Order Quantity (EOQ), Reorder Point (ROP), Total Inventory Cost (TIC) and Safety Stock (SS). The results showed that to meet the raw material needs of 91,375 kg during the research period, from January 2020 to December 2020 (12 months), the number of economical purchases/EOQ of wheat flour raw materials that had to be made by the Mie Dzohir factory in Bengkulu was as much as 5,372 kg for each order with a purchase frequency of 17 times for a period from January 2020 to December 2020. Reorders or reorder points (ROP) can also be determined, namely reordering should be done when 345 kg of inventory is in warehouse, with a lead time of 1 days so as not to hamper the company’s production process. The total inventory cost (TIC) can also be determined, namely the total cost of raw material inventory of Rp. 3.572.188, - therefore, it can save on inventory costs of Rp. 1.051.697,- .Safety stock (SS) of 95 kg which must be in the warehouse, this is intended therefore, there is no shortage of wheat flour raw materials if there is a delay in the delivery of raw materials.